Asuhan Keperawatan Pada An.M Dengan Gangguan Persyarafan : Epilepsi Diruang Edelwais Rsud Pandan Arang Boyolali - KUMONO, Joko; , Irdawati, S.Kep.,Ns.,M.Si.,Med (2015)
Background: Epilepsy is a disorder of the central nervous system that is characterized by the occurrence of spontaneous generation and periodic, Epilepsy is a recurrent seizure proximal two times or more without obvious cause attacks with intervals of more than 24 hours, due to loose electrical charge excesive in brain neurons. Objective: To determine the nursing care of patients with neurological disorders include epilepsy assesment, intervention, implementation, and evaluation of nursing. Results: After 3x24 hour nursing care for the results obtained risk of injury can be controlled , can choose activities that do not cause fatigue, families understand what to do in the event of seizures, low self esteem is resolved. Conclusion: Cooperation between the healthcare team and the patient/family is indispensable for the success of nursing care to patients, therapeutic communication can encourage patien and families more cooperative. Keywords: Epilepsy, Risk of Injury, Nursing Care